Three Documents of the Koinon of the Cities in Pontus - Ching-Yuan Wu (149th Annual Meeting of the Society of Classical Studies., 2018)
The earliest evidence for the Koinon of the Cities in Pontus, comprised of a group of cities in coastal Paphlagonia, is a Trajanic honorific inscription, which happens to be one of two lost "official documents – as Søren Sørensen (2016) describes them – that provide the full title of the koinon’s existence, as well as some indication that their findspots at Amastris and Heraclea were likely the metropoleis of the koinon (Sørensen 2016, p. 73- 74). Sørensen’s treatment of the two inscriptions, while brief, represents a trend in scholarship that is shifting away from the entrenched acadmic debate on the geographical extent of the elusive coastal Paphlagonian koinon, a century-long tradition which he artifully summarized as “a war of analysts and unitarians” (Sørensen 2016, p. 75-84). This paper takes a closer look at the contents of the two documents (Kalinka 1933, p. 73 no. 21; p. 95 no. 67), along with a reference to a krima issued by the koinoboulion in concert with the boule and demos of Heraclea (Kalinka 1933, p. 93 no. 69), in order to study the Koinon of the Cities in Pontus based on the information that could be elicited from the words of the koinon itself. While the documents concerning the Koinon of the Cities in Pontus provide only snippets of its operational aspects, including the eligibility of candidates, the preferences of the koinon assembly, and deeper involvement in affairs concerning civic training and testamentary execution, they together indicate that the Koinon was likely a permanent institution that did not convene or focus its operation solely on affairs pertaining to the honoring of the emperors or the organizing of festivities, as Marek supposed in his short treatment on the matter (Marek 2003, pp. 63-67). The degree of engagement of the Koinon on municipal affairs of its constituent communities is considerable: it took interest in the performances of its leading men in the Amastrian neoi, and it joined the boule and demos of Heraclea in honoring a citizen from Heraclea for volunteering to take up the koinon archierosyne. The invocation of the krima – a joint “opinion” of the koinoboulion and the Heraclean boule and demos – in the execution of a private will indicates that the authority of the Koinon of the Cities in Pontus was regarded as an important factor even in testamentary execution. This document in particular suggests that there must have been some degree of administrative integration between the Koinon of the Cities and its constituent communities. These findings help integrate the Koinon of the Cities in Pontus into the recent academic discourse concerning the role in provincial administration that the koina of the Greek East played during the Principate. Jürgen Deininger’s 1965 study on koina and concilia during the Principate argued that such provincial- level institutions as primarily ceremonial, with only some diplomatic functions in addition to the worship of the emperors organization of games in the emperors’ honor. Sporadic objections since the initial publication of his work have been recently tabulated and assessed by Babett Edelmann-Singer (2015), who convincingly rejected Deininger’s limiting interpretation of evidence concerning financial and administrative aspects already available to him, and further demonstrated how Deininger’s thesis require revision in light of new epigraphical discoveries, such as the lex portorii Lyciae (Takmer 2007). As Edelmann-Singer did not touch upon the Koinon of the Cities in Pontus extensively, nor did she take note of the evidentiary value of the three documents highlighted by Sørensen, the analyses of the three documents of the Koinon of the Cities in Pontus in this paper supplements her work in exploring the various aspects that were downplayed by Deininger or unknown to him.